(untitled) (Malay Literature, 2020)
Rich in culture as reflected in their material culture, the Dusun ethnic group of Sabah (previously known as North Borneo) possess a wealth of folktales in the form of oral narratives that are rapidly fading along with the storytellers themselves. This research project has been initiated to reverse this threat towards the non-material folk culture by collecting and analyzing the folk narratives, popularly referred to as tangon among the Dusun ethnic group in the district of Tambunan, Sabah. This paper also hopes to demonstrate a method of interpretation that takes into consideration the social and cultural background of the respondents (storytellers) and the influences that affect the narrated tales. The method involved the collection of 20 tangon from 13 storytellers who are Dusun ethnic informants residing in Kampung Sunsuron, Tambunan. The analysis demonstrates an attempt to understand the Dusun ethnic group’s perspective on the cycle of life, especially the elements of birth, initiation and death that are contained in their folk narratives. It is the objective of this paper to encourage a method of interpretation and collection that emphasizes on the storytellers’ social and cultural background and the integral part played by them in the creation of their folk narratives. Keywords: Tambunan Dusun, tangon, life cycle, birth, initiation, death